Macroeconomics - Dornbusch, Rudiger; Fischer, Stanley; Startz, Richard (Boston McGraw Hill, 1998)
This updated edition presents a view of macroeconomics at a level accessible for students. The book includes expanded coverage of economic growth and a new chapter on "new macroeconomics", which includes information on the unit root of GDP controversy, real business cycles and the new Keynesian sticky price theory. There is also a new chapter on financial markets and continued international coverage, with international examples throughout the text.
Keywords: Macroeconomics